A Note on Welfare Propositions in Economics - de Scitovszky, T. (Review of Economic Studies, 1941)
Journal Article A Note on Welfare Propositions in Economics Get access T. de Scitovszky T. de Scitovszky Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 9, Issue 1, November 1941, Pages 77–88, https://doi.org/10.2307/2967640 Published: 01 November 1941